Charlie Chaplin - Chaplin, Charlie (Alpha Video Distributors, 1992)
Charles Spencer Chaplin was born in London, England in 1889. Both of his parents were music hall entertainers. He was an only child. Chaplin, was a toddler when he learned his first vaudeville comedy routines. His first professional work was as one of the " Eight Lancashire Lads", a group of pre-teens who toured dance halls doing their act. At 17, he started working with a comedy group known as the " Karno Company". In 1913 while on tour with Karno Company he was spotted by Mack Sennet, the head of the Keystone Studios. Chaplin was immediately given a film contract. By the end of 1914, Chaplin had appeared in 35 Keystone Comedy shorts. The secret of Chaplin's success was his originality and ability to ad lib. Many of these films were made without scripts. During the year at the Keystone, Charlie Chaplin established himself as the " little man with the mustache, derby and a cane". By 1915 he was world famous with his unique walk and fantastic sense of comedic timing. The "Little Tramp" character was in full swing. Charlie Chaplin was perhaps one of the most influential progenitors of comedy in the history of film.